2015
DOI: 10.1074/jbc.m114.616359
|View full text |Cite
|
Sign up to set email alerts
|

p53 Protein-mediated Regulation of Phosphoglycerate Dehydrogenase (PHGDH) Is Crucial for the Apoptotic Response upon Serine Starvation

Abstract: Background: PHGDH encodes a key metabolic enzyme in the serine biosynthesis pathway and is frequently amplified in melanomas. Results: p53 transcriptionally represses PHGDH expression. Serine starvation promotes p53-mediated apoptosis in melanomas through PHGDH suppression. Conclusion: p53-mediated repression of PHGDH enhances the apoptotic response upon serine starvation in melanoma cells. Significance: The combination of the drugs activating p53 and serine deprivation could be a better treatment for melanoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 37 publications
2
94
2
Order By: Relevance
“…To identify metabolic targets of p53, the melanoma cell line A375 expressing wild-type p53 was either untreated or treated with Nutlin, and total RNA derived from these cells was subjected to RNA sequencing. In our previous study, we identified PHGDH from the RNA-sequencing result as a metabolic target of p53 that is critical for inducing the apoptotic response upon serine starvation (15). In addition, we also found that mRNA levels of SAT1 are significantly up-regulated upon p53 activation (Fig.…”
Section: Sat1mentioning
confidence: 67%
See 1 more Smart Citation
“…To identify metabolic targets of p53, the melanoma cell line A375 expressing wild-type p53 was either untreated or treated with Nutlin, and total RNA derived from these cells was subjected to RNA sequencing. In our previous study, we identified PHGDH from the RNA-sequencing result as a metabolic target of p53 that is critical for inducing the apoptotic response upon serine starvation (15). In addition, we also found that mRNA levels of SAT1 are significantly up-regulated upon p53 activation (Fig.…”
Section: Sat1mentioning
confidence: 67%
“…ChIP assays were performed as previously described in H1299 cells transfected with empty vector or pCIN4-p53 (15). Primers used for ChIP qPCR were SAT RE1 forward 5′-CAGTAGGGTTTCCGCCAAG-3′, SAT1 RE1 reverse 5′-AACCCGGAGGACAAAAGTG-3′; SAT RE2 forward 5′-TCCTGA-GTTTGCTTCCCACT-3′, SAT1 RE2 reverse 5′-GGTGTGTCCCCCAGTAACAT-3′; SAT RE3 forward 5′-CACTGATTCTCAACTGCCAAA-3′, SAT1 RE3 reverse 5′-CAGAAGCAGAGGAGGAAAAGG-3′; SAT RE4 forward 5′-CAAAAG-ACCACCCCTCACAT-3′, SAT1 RE4 reverse 5′-CCTAGGGCAGGAAGGGTAAC-3′;…”
Section: Methodsmentioning
confidence: 99%
“…In addition, TP53 promotes metabolic remodeling under serine starvation for cell proliferation (18,19). MDM2 also regulates serine metabolism during oxidative stress independent of p53 (20).…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been suggested that the p53 tumor suppressor gene inhibits PHGDH expression and consequently the de novo SSP [15,16]. A study using a human colon cancer cell line already demonstrated that a lack of p53 induced failure in dealing with serine starvation, proceeding to oxidative stress and impaired proliferation.…”
Section: Discussionmentioning
confidence: 99%